Nursing of a patient with acute mastitis during lactation treated by stone needle therapy combined with Traditional Chinese Medicine collapse stains (砭石疗法联合中药塌渍治疗哺乳期急性乳腺炎1例的护理体会) - ZHENG Ruiwen (郑睿文); CHEN Hong (陈宏); HE Jing (何静); XU Jingjin (徐京巾); ZHANG Jing (张敬); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the effect of stone needle therapy combined with Traditional Chinese Medicine (TCM) collapse stains in the treatment of acute mastitis during lactation. On the basis of risk assessment and routine nursing, a TCM external treatment, stone needle therapy combined with TCM collapse stains, was performed according to the TCM syndrome differentiation. The TCM external treatment is effective in relief of inflammation, local pain and symptoms of redness on the skin in patients with acute mastitis during lactation. (本文总结1例哺乳期急性乳腺炎患者行砭石治疗联合中药塌渍治疗的临床效果和护理经验。首先应完善对患者的护理评估, 做好常规护理工作, 基于辨病辨证实施中医外治法。砭石治疗及中药塌渍能够改善局部炎症, 有效缓解患者疼痛及乳房局部发红情况。)